Pengembangan Model Manajemen Risiko Terintegrasi untuk Inovasi Digital Perbankan Syariah - Gusti Oka Widana; Waliyudin (ITB AAS INDONESIA Surakarta, 2025)
This study aims to formulate and propose a comprehensive, integrated risk management model to address the challenges of digital innovation in Islamic banking. This research is motivated by the emergence of hybrid risk profiles and a significant governance gap resulting from siloed risk management practices among the IT Division, the Risk Management Division, and the Sharia Supervisory Board (DPS). This study employs a descriptive qualitative method using a library research approach. Data was collected through a documentary analysis of existing literature, encompassing scientific journals, industry standards (COSO ERM, COBIT), Sharia standards (AAOIFI, DSN-MUI Fatwas), and banking regulations (POJK). Data analysis was conducted via critical synthesis, focusing on gap analysis within existing frameworks to construct a new conceptual model. The finding of this study is the